2002
DOI: 10.1007/s00432-002-0322-9
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase (CYP19) expression in tumor-infiltrating lymphocytes and blood mononuclears

Abstract: The data obtained suggest that aromatase gene expression is presented in TIL at a rather low level. Nevertheless, this can have some functional significance for the estrogen-dependent growth of breast cancer tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The tumor-infiltrating lymphocytes are able to produce and release vascular endothelial growth factor (VEGF) and basic fibroblastic growth factor, which can induce lymphangiogenesis and angiogenesis and consequently could permit the dissemination of cancer cells through lymphatics to regional lymph nodes. [24][25][26][27][28] Bernstein et al 29 demonstrated that the aromatase (CYP19) gene is presented in tumor-infiltrating lymphocytes, and the presence of local oestrone formation could have some functional significance for the estrogendependent growth of breast cancer tissue, creating favorable environment for cancer cells. The presence of tumor-infiltrating lymphocytes in breast carcinomas and production of potentially immunoinhibitory cytokines such as IL-4, IL-10, and TGF-²1 has been demonstrated; this production by tumor-infiltrating lymphocytes in breast cancers exceeded that detected in benign breast lesions, suggesting a role for tumor-infiltrating lymphocytes in immunosuppression, creating a mechanism of immune escape for the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor-infiltrating lymphocytes are able to produce and release vascular endothelial growth factor (VEGF) and basic fibroblastic growth factor, which can induce lymphangiogenesis and angiogenesis and consequently could permit the dissemination of cancer cells through lymphatics to regional lymph nodes. [24][25][26][27][28] Bernstein et al 29 demonstrated that the aromatase (CYP19) gene is presented in tumor-infiltrating lymphocytes, and the presence of local oestrone formation could have some functional significance for the estrogendependent growth of breast cancer tissue, creating favorable environment for cancer cells. The presence of tumor-infiltrating lymphocytes in breast carcinomas and production of potentially immunoinhibitory cytokines such as IL-4, IL-10, and TGF-²1 has been demonstrated; this production by tumor-infiltrating lymphocytes in breast cancers exceeded that detected in benign breast lesions, suggesting a role for tumor-infiltrating lymphocytes in immunosuppression, creating a mechanism of immune escape for the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the rate-limiting step of steroidogenesis, mediated by steroidogenic acute regulatory protein (StAR), functions in myeloid cells, suggesting the capacity of these cells to synthesize steroids de novo [39,40]. However, in the absence of this step in other immune cells, steroidogenesis is carried out upon the availability of downstream intermediates such as androstenedione or dehydroepiandrosterone (DHEA) [41].…”
Section: Non-nuclear-receptor-mediated Effects Of Cholesterol Metabolmentioning
confidence: 99%
“…In experimental PH, dysregulated immunity in the form of deficient regulatory T-cell (Treg) activity contributes to increased inflammation [20]. Both alveolar macrophages and immune cells express steroidogenic enzymes including sulfatase and aromatase [119][120][121]. Inflammatory cytokines, prostanoids, and growth factors regulate the expression and activity of steroidogenic enzymes, and in turn, sex hormones 2-Methoxyestradiol in Pulmonary Arterial Hypertension: A New Disease Modifier DOI: http://dx.doi.org/10.5772/intechopen.86812 may influence the production and release of these autocrine/paracrine mediators [122].…”
Section: Anti-inflammatory and Immunomodulatory Effects Of 2mementioning
confidence: 99%